Hypogonadism in adolescent girls: treatment and long-term effects - Voutsadaki, Kleanthi; Matalliotakis, Michail; Ladomenou , Fani (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Hypogonadism in adolescent females presents as delayed puberty or primary amenorrhea. Constitutional delay of growth and puberty, hypogonadotropic hypogonadism and hypergonadotropic hypogonadism represent the principal differential diagnosis of delayed puberty. Girls with hypogonadism require hormone replacement therapy to initiate and sustain puberty. We aimed to provide a brief review concerning treatment for female adolescents with hypogonadism and further to focus on current data regarding long-term effects of therapy. Methods: The published studies and articles of the international literature were used regarding the approach to adolescent girls with hypogonadism. Results: The aim of therapy is the development of secondary sexual characteristics and achievement of target height, body composition and bone mass, to promote psychosexual health and, finally, to maximize the potential for fertility. Hypogonadal females need long-term HRT, so it is of great importance to fully define risks and benefits of therapy. Conclusions: The optimal pubertal induction in women contains both estrogens and progesterone regimens. Different therapeutic options have been described over the years in the literature, but larger randomized trials are required in order to define the ideal approach. The latest acquisitions in the field seem to propose that transdermal 17β-estradiol and micronized progesterone present the most physiological formulations available for this purpose. Further studies and follow up are needed concerning the long-term effects of HRT in adolescents.